Synthesis of hydroxyapatite from hard clams shell (Meretrix spp.) using hydrothermal method as a dental implant coating biomaterials - Zefania Riri; Patrinela Hilda; Lalak Tarbiyatun Nasyin Maleiva; Intan Syahbanu; Syahrul Khairi; Kiki Aristi (Jurnal Rekayasa Proses, 2025)
Biomaterials that can be used as coatings on dental implants are hydroxyapatites. One of the natural substances used in the synthesis of hydroxyapatite is the ale-ale shell, which has a substantial calcium content of 93,444%. The hydroxyapatite synthetic was carried out using a hydrothermal method that uses the calcium precursor (Ca) of the ale-ale shell and phosphate precursors (P) derived from (NH4)2HPO4, as well as NH4OH as a pH regulator. This research uses the influence variables of CaO/(NH4)2HPO4 concentration (0.67; 1.67; and 2.67) and pH (11, 12, and 13). The results of the FTIR analysis showed that the typical absorption peaks of hydroxyapatites are , OH-, and group absorptions. XRD analysis results showed the formation of major HAp peaks that correspond to ICDD data 01-072- 1243, with the highest peaks in succession appearing at angles 31,74; 31,67; and 31,64°. The crystal size is 35,25; 123,39; and 55,81 nm with degrees of crystallinity in sequence of 87,28; 91,67; and 95,09° and has a hexagonal crystal shape. Hydroxyapatite synthesis with ale-ale shell waste raw materials by hydrothermal method gives the best results at a concentration of CaO/(NH4)2HPO4 2.67-pH 13.